The cardioprotective effects of carvedilol on ischemia and reperfusion injury by AMPK signaling pathway - Haiyan Hu (Biomedicine & Pharmacotherapy, 2019)
Carvedilol, a third generation beta blocker, is in clinical use for heart failure patients. However, besides adrenergic receptor blockade, the pharmacological effects of carvedilol on cardiomyocytes remain unknown. AMP-activated protein kinase (AMPK) is an emerging target recognized for heart failure treatment. The mechanical properties and intracellular Ca2+ properties were measured in isolated cardiomyocyte contractile functions in response to ischemic stress. Treatment of cardiomyocytes with carvedilol augmented phosphorylation of AMPK and downstream acetyl CoA carboxylase (ACC), and ameliorated hypoxia-induced impairment in maximal velocity of shortening (+dL/dt) and relengthening (-dL/dt), and the impaired peak height and peak shortening (PS) amplitude caused by hypoxia. Carvedilol treatment improved calcium homeostasis with rescuing the peak Ca2+ signal, the maximum rate of Ca2+ change during contraction (+dF/dt) and the maximum rate of Ca2+ change during relaxation (-dF/dt) under hypoxia conditions. In mouse hearts perfused ex vivo with carvedilol, the function of post-ischemia left ventricle was improved and an augmentation in myocardial glucose uptake and glucose oxidation, and inhibition of fatty acid oxidation during ischemia and reperfusion. The protective effect of carvedilol was further supported in an in vivo regional ischemia model by ligation of left anterior descending coronary artery (LAD), mice treated with carvedilol followed by LAD occlusion and reperfusion showed significant size reduction in infarcted myocardium and improved cardiac functions. Therefore, Carvedilol as a clinical drug can modulate cardiac AMPK signaling pathway to reduce ischemic insults by ischemia and reperfusion.